Optimization of Deposition Parameters for Ni-P-WC-BN(h) Composite Coatings via Orthogonal Experimentation and Wear Behavior of the Optimized Coating - Yingyue Li; Zehao Liu; Yana Li; Jinran Lin (Metals)
Ni–P–WC–BN(h) nanocomposite coatings were fabricated on 20CrMnTi substrates using ultrasonic-assisted pulsed electrodeposition. 20CrMnTi is a low-carbon steel that is commonly used in the manufacturing gears and shaft components. To enhance the wear resistance and extend the service life of such mechanical parts, ultrasonic-assisted pulsed electrodeposition was employed as an effective surface modification technique. The microhardness, phase structure, surface morphology, and wear behavior of the coating were also characterized. An orthogonal experimental design was employed to examine the effects of current density, bath temperature, ultrasonic power, and pulse duty cycle on the microhardness and wear behavior of the coatings, aiming to optimize the deposition parameters. The optimal process combination was identified as a current density of 3 A·dm−2, a bath temperature of 55 °C, an ultrasonic power of 210 W, and a duty cycle of 0.7. Under these conditions, the coatings exhibited enhanced hardness and wear resistance. Based on the optimized parameters, additional tribological tests were conducted under various operating conditions to further evaluate wear performance. The results showed that the dominant wear mechanisms were chemical wear and adhesive wear. This study offers new insights into the fabrication of high-performance nanocomposite coatings and expands the application scope of ultrasonic-assisted pulsed electrodeposition in multiphase composite systems.